Visualizing Mitochondrial FoF1-ATP Synthase as the Target of the Immunomodulatory Drug Bz-423 - Starke, Ilka; Glick, Gary D.; Börsch, Michael (Frontiers in Physiology, 2018)
Targeting the mitochondrial enzyme FoF1-ATP synthase and modulating its catalytic activities with small molecules is a promising new approach for treatment of autoimmune diseases. The immunomodulatory compound Bz-423 is such a drug that binds to subunit OSCP of the mitochondrial FoF1-ATP synthase and induces apoptosis via increased reactive oxygen production in coupled, actively respiring mitochondria. Here we review the experimental progress to reveal the binding of Bz-423 to the mitochondrial target and discuss how subunit rotation of FoF1-ATP synthase is affected by Bz-423. Briefly, we report how Förster resonance energy transfer (FRET) can be employed to colocalize the enzyme and the fluorescently tagged Bz-423 within the mitochondria of living cells with nanometer resolution.